PERAN KEY OPINION LEADER TERHADAP KEPUTUSAN PEMBELIAN - Lingga Yuliana (Politeknik Ubaya, 2023)
In general, consumers will decide to purchase goods and services due to low pricing and in conjunction with their earnings level. However at the moment, consumers rely their decision to purchase a piece of apparel on the branded product and the personality who represents the brand. The intention of this study is to use case studies that involve actual consumers to evaluate how customers' decisions to make purchases under the Clarin The Label brand are influenced by key opinion leaders. Similar studies regarding Key Opinion Leaders on Consumer Purchase Decisions have not been found by researchers regarding their partial and simultaneous correlations. So with this it can be novelty in research so that it becomes new knowledge for consumers. This research used a descriptive qualitative methodology. In this study, three respondents were selected using the purposive sample method. The Visibility, Credibility, Attraction, and Power components have been appropriately applied in Rini Florencia's illustration based on the VisCAP model. With this, the Claryn The Label Key Opinion Leader encourages consumers' decision-making over their purchases.